2018
DOI: 10.2754/avb201887030261
|View full text |Cite
|
Sign up to set email alerts
|

Ankaferd blood stopper accelerates deep second degree burn wound healing in rats

Abstract: In this study, the effects of Ankaferd Blood Stopper (ABS) and silver sulphadiazine (SSD) cream on burn wound healing were investigated in rats. A total of 24 outbred, male, Sprague-Dawley rats were randomly allocated to (1) ABS, (2) SSD, and (3) control groups. Bilateral burn wounds were created near the caudal border of the scapula. Wounds in each group were treated daily with sponges soaked in ABS solution, 1% SSD cream, or saline, respectively. On days 0, 7, 14, 21, and 28, unhealed wound area was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[14] The comparison between the groups in our study showed that ABS was statistically significantly superior with respect to histopathological evaluation and recovery duration compared with the previously proven SSD. Kaya et al [16] and Topal et al [17] have previously demonstrated that even though the ABS and control groups are similar with respect to wound healing on day 7, ABS is statistically superior on day 14. In contrast, Topal et al [17] could not determine any difference between ABS and SSD in burn wounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] The comparison between the groups in our study showed that ABS was statistically significantly superior with respect to histopathological evaluation and recovery duration compared with the previously proven SSD. Kaya et al [16] and Topal et al [17] have previously demonstrated that even though the ABS and control groups are similar with respect to wound healing on day 7, ABS is statistically superior on day 14. In contrast, Topal et al [17] could not determine any difference between ABS and SSD in burn wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Kaya et al [16] and Topal et al [17] have previously demonstrated that even though the ABS and control groups are similar with respect to wound healing on day 7, ABS is statistically superior on day 14. In contrast, Topal et al [17] could not determine any difference between ABS and SSD in burn wounds. On the other hand, in our study, ABS had a shorter recovery time than SSD based on 50% and 80% of re-epithelization rates.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the mean percentage of wound contraction in the ABS and SSD groups was significantly higher at 14, 21 and 28 days than in the control group. They reported that, wound healing is characterized by a decrease in neutrophil count and an increase in vascular count, and that ABS, as well as SSD, can be successfully used in burn wound healing [24]. In a study by Akalin et al, they created a full-thickness wound defect and applied ABS.…”
Section: Kido Et Al Created Diabetes By Applying Streptozotocin Tomentioning
confidence: 99%
“…They showed that the mean percentage of wound contraction in the ABS and SSD groups was significantly higher than in the control group on days 14, 21, and 28 and suggested that ABS could be successfully used for burn wound healing besides (SSD). 52 ABS can improve the wound-healing process via providing inhibition of extra cellular matrix-degrading enzymes during wound repair. Moreover, ABS enhanced the stimulated migration of 3T3 fibroblasts to an artificial wounded area.…”
Section: Ankaferd Hemostat (Abs) In Wound Healingmentioning
confidence: 99%